Antonio Piñero and Javier Alonso. How Christianity Was Born: The True History of Its Origins, from Jesus to the Creation of the Church. Barcelona, Shakelton Books, S. L., 2025, 288 pp. ISBN: 978-84-1361-330-7 - Segura Jaubert, José Marco (2026)
The work introduces the reader to the Jewish context that gave rise to the figure of Jesus of Nazareth, who became the driving force behind Christianity. It also delves into the different branches of Christianity in its early stages, revealing that the movement was not a monolith, but a complex and multifaceted historical phenomenon where, over the centuries, the Pauline tradition ultimately prevailed.